Implementation of Regency/Municipal Bawaslu Authority in Handling Election Criminal Violations Committed by Children - Darma, Darma; Bariun, La Ode; Siregar, Winner (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
The study aims to determine the authority of Regency/Municipal Bawaslu in handling election criminal violations and election criminal violations and to find out the implementation of the handling of election criminal violations and election criminal violations committed by children in the 2019 and 2020 elections. Cities in handling election criminal violations, starting from receiving and following up on findings and reports related to alleged election criminal violations, examining and reviewing election criminal violations, collecting evidence, requesting information needed from related parties or clarification, and forwarding the results review of findings and reports to authorized agencies for follow-up. Meanwhile, the handling of election criminal violations is carried out at each stage of the election implementation based on findings and reports. Following up on reports related to the alleged election criminal violations by conducting studies and clarifications, these were then forwarded to Gakkumdu. Meanwhile, the implementation of the handling of election criminal violations and election crimes committed by children during the 2019 elections in Bombana Regency as well as the 2020 elections in South Konawe Regency and East Kutai Regency used diversion efforts at the investigative level. The Diversion process is conducted through deliberations involving children and their parents or guardians, the Gakkumdu Sentra Team, Community Advisors, and the community. This provision refers to the formal provisions of the juvenile justice system as stipulated in Law Number 11 of 2012.